ZrN and ta-C Coatings on Titanium for Biomedical Applications: Improved Adhesion, Corrosion, Antibacterial Activity, and Cytotoxicity Properties - Aslan, Naim; Aksakal, Bünyamin; Cihangir, Salih; Çetin, Fadime; Yılmazer, Yasemin (Springer Nature, 2023)
Commercially pure titanium (CP-Ti) is extensively used in biomedical applications. However, numerous qualities, including mechanical strength, corrosion resistance, and wear resistance, must be established for long-term performance as an implant material. This study investigates the enhancement of surface properties of CP-Ti through physical vapor deposition (PVD) with ZrN and ta-C (tetrahedral amorphous carbon). Among the coatings, ZrN revealed best overall results, such as adhesion, corrosion, microhardness, and wettability, excluding cell viability when compared to ta-C. E. coli and S. aureus were employed for antibacterial activity and MTS cell viability experiments. Compared to α-titanium, hardness tests revealed 91% increase in ZrN coating, and %22 increase in ta-C coating. Super-hydrophobicity and excellent antibacterial activity were found for ZrN coatings in comparison to ta-C. These findings emphasize the potential of ZrN and ta-C coatings to improve the surface properties of titanium, encouraging it to be used in biomedical devices. Graphical abstract: [Figure not available: see fulltext.].
Keywords: Antibacterial activity; Cell viability; Corrosion; PVD; α-Titanium